Pathophysiological Role of Vimentin Intermediate Filaments in Lung Diseases - Surolia, Ranu; Antony, Veena B. (Frontiers in Cell and Developmental Biology, 2022)
Vimentin intermediate filaments, a type III intermediate filament, are among the most widely studied IFs and are found abundantly in mesenchymal cells. Vimentin intermediate filaments localize primarily in the cytoplasm but can also be found on the cell surface and extracellular space. The cytoplasmic vimentin is well-recognized for its role in providing mechanical strength and regulating cell migration, adhesion, and division. The post-translationally modified forms of Vimentin intermediate filaments have several implications in host-pathogen interactions, cancers, and non-malignant lung diseases. This review will analyze the role of vimentin beyond just the epithelial to mesenchymal transition (EMT) marker highlighting its role as a regulator of host-pathogen interactions and signaling pathways for the pathophysiology of various lung diseases. In addition, we will also examine the clinically relevant anti-vimentin compounds and antibodies that could potentially interfere with the pathogenic role of Vimentin intermediate filaments in lung disease.